Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

given that f(x)=4x-3 and g(x)= (2x-1)/3 solve for g(f(2))

Sagot :

To solve g(f(2)), we need to solve for f(2) as:

f(x) = 4x - 3

Replacing x by 2, we get:

f(2) = 4(2) - 3

f(2) = 8 - 3

f(2) = 5

Now g(f(2) is equal to g(5), so:

[tex]g(x)=\frac{2x-1}{3}[/tex]

So, replacing x by 5, we get:

[tex]\begin{gathered} g(x)=\frac{2(5)-1}{3} \\ g(x)=\frac{10-1}{3} \\ g(x)=\frac{9}{3} \\ g(x)=3 \end{gathered}[/tex]

Answer: g(f(2)) = 3